BENCANA ASAP DI INDONESIA: - Abdul Rahman (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2012)
This articulation tries to expose the crisis about the smoke disaster in Indonesia which can exacerbate political relations between the Indonesia-Malaysia countries. This is important because the government and the people of Indonesia are often trapped in various problems that are actually simple. However, due to political miscommunication between countries coupled with the lack of coordination between bureaucracies, the problem that is actually simple is actually growing and complex.